Case Study : DNR Lekor Sdn Bhd / Nurul Izzah Aishah Ismail - Ismail, Nurul Izzah Aishah (2021)
This reports include the background profiles of DNR Lekor Sdn Bhd and also their four entrepreneurial competencies. DNR Lekor is one of the most famous producer of ‘keropok lekor’ in Terengganu. They produced their products targeting the whole community inside and outside of Terengganu. They have achieved countless achievements that prove all of their hard works in order to grow their business. Going through many hardships, DNR Lekor shined their entrepreneurial competencies namely initiative, sees and acts on opportunities, systematic planning and problem-solving. These competencies eventually highlight their journey in making their products well-recognize and also expanding their business. Having the skills to slay all the competencies, DNR Lekor sure are unbeatable by other companies in the same industry.